2006
DOI: 10.1162/isec.2006.30.4.152
|View full text |Cite
|
Sign up to set email alerts
|

Desperate Times, Desperate Measures: The Causes of Civilian Victimization in War

Abstract: Despite normative and legal injunctions against targeting civilians in war, as well as doubts regarding the effectiveness of such strategies, belligerents have frequently turned their guns on noncombatants. Two variables—desperation to win and to save lives on one's own side in protracted wars of attrition, and the intention to conquer and annex enemy territory—explain this repeated resort to civilian targeting. According to the desperation logic, costly and prolonged wars of attrition cause states to become i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(71 citation statements)
references
References 19 publications
3
66
1
1
Order By: Relevance
“…It also deviates from previous discussions that are more concerned with the reasons for violence against noncombatants in past conflicts (see Downes 2006) by pointing to such violence that will occur in future conflicts. The problematic nature of weaponizing noncombatants could be addressed by some of the scholarship regarding self-defense in the case of 'innocent' threats (see Benbaji 2005;Thomson 1991), which also fits into some of the recent discussions on killing in times of war (see McMahan 2009).…”
Section: The Moral Conundrum Of the Noncombatantcontrasting
confidence: 85%
“…It also deviates from previous discussions that are more concerned with the reasons for violence against noncombatants in past conflicts (see Downes 2006) by pointing to such violence that will occur in future conflicts. The problematic nature of weaponizing noncombatants could be addressed by some of the scholarship regarding self-defense in the case of 'innocent' threats (see Benbaji 2005;Thomson 1991), which also fits into some of the recent discussions on killing in times of war (see McMahan 2009).…”
Section: The Moral Conundrum Of the Noncombatantcontrasting
confidence: 85%
“…scans to study moral decision making, Greene of an individual's decision can cause a particular individual or group of people to suffer serious bodily harm; impersonal dilemmas exist when harm may come through only an indirect effect of their actions+ Dilemmas are "easy" if there is a moral case for only one option, and "hard" if a moral case can be made for both options+ Greene found that when participants responded to impersonal dilemmas, areas of the brain most associated with conscious cognition were active+ 47 When easy moral dilemmas were confronted, areas of the brain associated with automatic processing and emotion were active, and decisions were made extremely quickly+ However, when participants were confronted with hard moral dilemmas and they decided that a moral violation was necessary, areas of the brain associated with both emotion and conscious cognition were active, and individuals demonstrated long reaction times+ 48 The evidence that emotion and automatic processing were the primary active processor in unconflicted moral dilemmas is strongly suggestive that taboos are processed in ways strikingly different from most other decisions+ The evidence that moral conflicts cause a different processing pattern, one that is both emotional and consciously cognitive, is likewise striking evidence that people respond to normative conflicts in yet different ways+ Taken together, this evidence suggests that when pitted against another taboo or fundamental value, taboos may lose their stigma+ This fact alone does not resolve the ubiquity of norms problem, inasmuch as it does not provide an a priori way of predicting which taboo will be maintained and which taboo will be violated+ The desperation to save something may overwhelm constraints against using forbidden weapons, 49 but this may not always be the case+ Psychological analysis does, however, provide further insight into how decision makers may respond to this decision problem+ First, Baron, Greene, and their colleagues all argue that these dilemmas produce decision making with a utilitarian character+ 50 Second, maintaining the tragic character of the trade-off requires maintaining an interest in the values underlying each taboo+ Third, the emotions elicited when an individual confronts a tragic tradeoff-particularly if it is unexpected-may encourage further analysis of the problem+ Together, these factors suggest that decision makers confronting competing taboos may craft options that try to jointly maximize the values encompassed by the competing taboos, even as a taboo is violated+ This may be done by trying to minimize the violation in some way or by trying to mitigate its effects+ For instance, if a leader believes that they confront a choice between losing sacred land and using a forbidden weapon, in these tragic circumstances a means of dividing it that nev- Downes's 2006 finding that desperation to win and avoid losses on one's side are major explanations for killing civilians is congruent with this intuition+ Although Mandel 1993 finds gas being used to terrorize civilians and irregular forces, in his only case involving a conventional war-the Iran-Iraq war-it was used in desperation to avoid defeat+ 50+ See Baron and Leshner 2000;and Greene et al+ 2004+ ertheless preserves its core "sacredness" may be found to be acceptable+ Alternatively, if the forbidden weapon is to be used, decision makers may try to limit the extent of its use+ Tragic violations are likely to be the minimal violation decision makers believe will allow them to retain both their political goals and their character+ Because it may often seem easier to mitigate the effects of taboo weapons, tragic trade-offs may tend to favor weapons taboos+ 51 When dealing with weapons of mass destruction, however, even a...…”
Section: Normative Conflict and The Limits Of Normative Prohibitionsmentioning
confidence: 99%
“…Realists disagree with all of these views because they see the pressures of international competition to be so great that variations in domestic system will not influence policy during wartime. Downes (2006) argues that democracies have adopted strategies that kill enemy civilians because they face domestic pressure to end wars quickly, a pressure that exceeds the audience costs of a violation. The pattern of compliance by democracies tests the three perspectives: do they comply more often generally--the constructivist position, do they comply more often when they have a legal obligation--the liberal position, or are they no different from other types of states--the realist view.…”
Section: An Institutional View Of Treaties and Compliancementioning
confidence: 99%